MaqÄá¹£id al-SharÄ«â€™ah Values in al-MÄwardÄ«â€™s Concept of the Caliphate - Pramono, Muhamad Fajar; Sahidin, Amir (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
This article aims to reveal the values of maqÄá¹£id al-sharÄ«'ah in al-MÄwardÄ«'s concept of the caliphate. He emphasizes the relationship between politics and maqÄá¹£id al-sharÄ«'ah, both of which aim to realize the benefit. Through literature study using the descriptive-analytical method, this paper finds that his basic concept of the caliphate is influenced by his understanding of maqÄá¹£id al-sharÄ«'ah, including maqÄá¹£id al-imÄmah, wasÄ«lah legal status, and maá¹£laá¸¥ah rules. All three are criteria and conditions that a leader meets. He succeeded in formulating a series of prerequisites for a leader to realize the benefit of the people. These prerequisites are in line with the substance of maqÄá¹£id al-sharÄ«'ah.